FACTORS THAT INFLUENCE ELDERS WITH MOBILITY IMPAIRMENT TO UTILIZE MEDICAL REHABILITATION SERVICES - Ekua Bentsiwaa Baiden- Amissah,; Priscilla Adomako Gyasi,; Lulin Zhou, (EPRA International Journal of Research and Development (IJRD), 2022)
The elderly population continually grows globally, necessitating health systems that cater to their needs, including medical rehabilitation since they are more susceptible to being mobility impaired which has been linked to a reduced quality of life for the elderly, rendering them reliant on others for basic daily life needs. Lack of rehabilitation for an impairment can lead to disability but most African countries struggle to provide rehabilitation services for people with diverse impairments so this leaves elders with mobility impairment at a great disadvantage. The study aims to identify the factors that influence mobility impaired elders to utilize medical rehabilitation services in the Ho Municipality of Ghana. METHODOLOGY:A qualitative study with 25 subjects purposively sampled were interviewed at the Ho Regional Hospital, and results analysis were carried out thematically. 5 rehabilitation therapists were interviewed on challenges faced when administering medical rehabilitation services provided at the facility whiles 20 elders with mobility impairment were interviewed on considered before using medical rehabilitations of the facility. Nvivo version 12 was used to evaluate the analysis. RESULTS: Organizational challenges like not enough skilled workers created more workload for the rehabilitation therapists. The elders with mobility impairment identified personal and environmental factors affected their use of the services. RECOMMENDATION: The study suggests that specialized health facilities for elders with need to be established with a focus on diverse medical rehabilitative services for those with mobility impairment. Comprehensive courses must also be designed to train skilled therapists to fill working positions that these new facets will create.